1966
DOI: 10.1113/jphysiol.1966.sp008019
|View full text |Cite
|
Sign up to set email alerts
|

The blood flow and oxygen consumption of brown adipose tissue in the new‐born rabbit

Abstract: 1. A direct method for measuring venous outflow from brown adipose tissue in anaesthetized new-born rabbits is described.2. During noradrenaline infusion the mean blood flow through brown adipose tissue increased from 87 to 360 ml./100 g tissue (wet wt.).min, and the mean rate of oxygen consumption of brown adipose tissue rose from 9.3 to 60 ml. O(2)/100 g tissue.min.3. During cold exposure the mean blood flow through brown adipose tissue increased from 90 to 304 ml./100 g tissue.min.4. The mean cardiac output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
1

Year Published

1974
1974
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 13 publications
6
69
1
Order By: Relevance
“…, As a consequence of the changes in metabolic requirements and V02, cardiovascular function and blood gases were also influenced by ambient temperature. The 20% increase in heart rate and cardiac output observed in room air at the lower temperature was probably due to the sympathetic stimulation that mediated the increase in brown fat metabolism (10). Inasmuch as it has been shown that the reserve capacity for increasing cardiac output is decreased in the newborn period, the increase in cardiac output secondary to the exposure to cool environment could considerably affect the potential-circulatory reserve of the normoxic newborn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, As a consequence of the changes in metabolic requirements and V02, cardiovascular function and blood gases were also influenced by ambient temperature. The 20% increase in heart rate and cardiac output observed in room air at the lower temperature was probably due to the sympathetic stimulation that mediated the increase in brown fat metabolism (10). Inasmuch as it has been shown that the reserve capacity for increasing cardiac output is decreased in the newborn period, the increase in cardiac output secondary to the exposure to cool environment could considerably affect the potential-circulatory reserve of the normoxic newborn.…”
Section: Discussionmentioning
confidence: 99%
“…Nonshivering thermogenesis is known to be very potent in the newborn lamb and regresses a few weeks after birth (3). Cold exposure is a potent activator of brown fat lipase (12,21), with marked increase in 0 2 uptake in the brown fat both as a result of an increase in blood flow and Oz extraction (10). During hypoxia, brown fat metabolism is inhibited (5,10) and Oz uptake is decreased in brown fat, as a result of both a decrease in blood flow and in oxygen extraction (10).…”
Section: Discussionmentioning
confidence: 99%
“…If the tachycardia were in fact caused by increased catecholamine production or adrenergic discharge, inotropic responsiveness to catecholamines must have been blunted, because adrenergic stimulation normally increases cardiac output as well as causing tachycardia. Blunting of adrenergic responsiveness has been described in the metabolism of brown fat under hypoxemic conditions (50). Cardiovascular responsiveness to a and 0 adrenergic stimulation during chronic hypoxemia should be studied to fully explain these findings.…”
mentioning
confidence: 99%
“…In the present study, an increase in the plasma concentration of T× following cold exposure is likely to be the result of cold stimulation of the hypothalamic-pituitary-thyroidal axis (Hefco et al 1975;Cabello, 1983). At 4 days of age effects of hypoxia on metabolism and thyroid hormone secretion may be exacerbated as a result of a decrease in Oµ extraction, blood flow (Heim & Hull, 1966) and therefore T× production (Fernandez et al 1987) by brown adipose tissue.…”
Section: Statistical Analysesmentioning
confidence: 90%